Antithrombotic therapy after percutaneous coronary intervention in patients with atrial fibrillation: an individual patient data network meta-analysis - Mauro Chiarito; Roxana Mehran; Michael C Gibson; Christopher P Cannon; Renato D Lopes; Samantha Sartori; Angelo Oliva; Kenneth Smith; Yihan Feng; Joshua Lampert; Andreas Goette; Adnan Kastrati; et al. (European Heart Journal, 2026)
Abstract Background and aims Randomized trials demonstrated that in patients with atrial fibrillation (AF) undergoing percutaneous coronary intervention (PCI) direct oral anticoagulants (DOAC) and a P2Y12 inhibitor reduce bleeding compared with vitamin K antagonist (VKA) plus dual antiplatelet therapy (DAPT) with no increase in ischemic risk; however, important gaps in knowledge remain, limiting certainty and generalizability of these findings. Methods In this patient-level meta-analysis of randomized trials evaluating antithrombotic strategies in patients with AF undergoing PCI, Cox proportional hazard models, stratified by trial, were used to estimate hazard ratios and 95% confidence intervals (HR, 95%CI). The primary efficacy and safety outcomes were the composite of cardiovascular death, myocardial infarction, or stroke, and TIMI major bleeding, respectively. The study was registered in PROSPERO (CRD420251130025). Results Six trials (10,634 patients) comparing DOAC plus P2Y12 inhibitor (4,083), VKA plus single antiplatelet therapy (SAPT, 1,247), VKA plus DAPT (3,715), and DOAC plus DAPT (1,589) were included. The transition from DAPT to SAPT was recommended at 1 (1-3) and 3 (1-7) days in the DOAC plus P2Y12 inhibitor and VKA plus SAPT groups, respectively. At 1 year, the risk of the primary efficacy outcome did not differ across the antithrombotic strategies (reference group: VKA plus DAPT; DOAC plus P2Y12 inhibitor: HR 1.16, 95%CI 0.97–1.41; VKA plus SAPT: 1.14, 0.85–1.54, DOAC plus DAPT: 0.99, 0.75–1.30), without any statistically significant interaction between treatment effects and all prespecified subgroups, including age, sex, bleeding risk, and thrombotic risk. However, 14-day landmark analysis showed an increased risk of myocardial infarction and definite/probable stent thrombosis in patients receiving DOAC plus P2Y12 inhibitor or VKA plus SAPT in the early phase after PCI. DOAC plus P2Y12 inhibitor reduced the risk of the primary safety outcome compared with VKA plus DAPT (0.48, 0.38– 0.65) and VKA plus SAPT (0.62, 0.40–0.97); only a borderline reduction was observed compared to DOAC plus DAPT (0.66, 0.44–1.01). DOAC plus P2Y12 inhibitor reduced intracranial hemorrhage compared with VKA plus DAPT (0.21, 0.07–0.64). Conclusions In patients with AF undergoing PCI, the risk of cardiovascular death, myocardial infarction, or stroke did not significantly differ according to whether patients received a DOAC or VKA, whereas a modest increase in risk with single compared with dual antiplatelet therapy cannot be excluded, given the higher risk of early coronary events. DOACs compared with VKAs reduced the risk of bleeding across all severity grades, including intracranial hemorrhage, whereas omission of a second antiplatelet agent reduced the risk of TIMI major or minor bleeding.